Instilling Cultural Appreciation in Early Childhood Through Teaching Modules Based on Local Wisdom - Yuliani, Yuliani; Herlina, Herlina; Bachtiar, Muhammad Yusri; Samputri, Salma (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2025)
This study aims to develop a teaching module based on local wisdom that can enhance cultural literacy in early childhood education at Al-Azzam Islamic Kindergarten in Makassar. Cultural literacy in early childhood is crucial for shaping children’s character and cultural identity; however, many early childhood education (ECE) teachers have not fully integrated local wisdom into their teaching. This research uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to develop a teaching module that combines elements of local culture and technology to enhance children's engagement. The findings indicate that the developed teaching module based on local wisdom is effective in improving children's cultural literacy, with significant improvements in the recognition of cultural symbols, participation in cultural activities, and appreciation for cultural diversity. This study also emphasizes the importance of integrating local culture into the ECE curriculum as a way to enrich children's learning experiences and strengthen their character. These findings make a significant contribution to the development of a more contextually relevant ECE curriculum that aligns with the cultural background of children in Indonesia